2004
DOI: 10.2166/wst.2004.0847
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-based, hollow-fiber membrane biofilm reactor for reduction of perchlorate and other oxidized contaminants

Abstract: Many oxidized pollutants, such as nitrate, perchlorate, bromate, and chlorinated solvents, can be microbially reduced to less toxic or less soluble forms. For drinking water treatment, an electron donor must be added. Hydrogen is an ideal electron donor, as it is non-toxic, inexpensive, and sparsely soluble. We tested a hydrogen-based, hollow-fiber membrane biofilm reactor (MBfR) for reduction of perchlorate, bromate, chlorate, chlorite, chromate, selenate, selenite, and dichloromethane. The influent included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(66 citation statements)
references
References 41 publications
0
66
0
Order By: Relevance
“…Among these limitations are low syngas kLa, low cell-biomass, sporulation, as well as substrate and product inhibition. Engineering syngas fermenting microorganisms for enhanced biofilm development can help overcome their inherently low biomass yield while enabling the use of reactors with enhanced gas mass transfer rates such as airlift reactors [59] or membrane biofilm reactors [60] as well as other types of biofilm-based reactors suitable for syngas fermentation [15,57]. More effective biofilms can be formed by increased exopolysaccharide production [61] or by manipulating other factors that are known to modulate biofilm formation in Clostridium species [62].…”
Section: Strain Engineering To Obtain Desired Production Phenotypesmentioning
confidence: 99%
“…Among these limitations are low syngas kLa, low cell-biomass, sporulation, as well as substrate and product inhibition. Engineering syngas fermenting microorganisms for enhanced biofilm development can help overcome their inherently low biomass yield while enabling the use of reactors with enhanced gas mass transfer rates such as airlift reactors [59] or membrane biofilm reactors [60] as well as other types of biofilm-based reactors suitable for syngas fermentation [15,57]. More effective biofilms can be formed by increased exopolysaccharide production [61] or by manipulating other factors that are known to modulate biofilm formation in Clostridium species [62].…”
Section: Strain Engineering To Obtain Desired Production Phenotypesmentioning
confidence: 99%
“…Our previous research showed that hydrogen-based bromate reduction occurs under denitrifying conditions (Nerenberg and Rittmann, 2004). The objectives of this research were to (1) determine whether a hydrogen-based, denitrifying membrane biofilm reactor (MBfR) can reduce bromate to below the 10-mg/L treatment objective; (2) assess the effects of pH, nitrate, nitrite, and bromate on bromate reduction rates; (3) determine the kinetics of hydrogen-based bromate reduction under denitrifying conditions; (4) explore bromate reduction in a pure-culture, denitrifying MBfR.…”
Section: Introductionmentioning
confidence: 99%
“…In some of these processes, preozonation is applied to improve the biodegradability of refractory organic matter (25,35,37,43). In other processes, termed stimulated biological treatment processes in the current study, electron donors are added to support microbial activity for the removal of contaminants that can serve as electron acceptors, such as nitrate (20), perchlorate (7,30), and other oxidized anions (34).…”
mentioning
confidence: 99%